2017
DOI: 10.1159/000471891
|View full text |Cite
|
Sign up to set email alerts
|

Should We Screen for Janus Kinase 2 V617F Mutation in Cerebral Venous Thrombosis?

Abstract: Background: The presence of Janus Kinase 2 (JAK2) V617F mutation represents a major diagnostic criterion for detecting myeloproliferative neoplasms (MPN) and even in the absence of overt MPN, JAK2 V617F mutation is associated with splanchnic vein thrombosis. However, the actual prevalence and diagnostic value of the JAK2 V617F mutation in patients with cerebral venous thrombosis (CVT) are not known. The aims of this study were to assess the prevalence of JAK2 V617F mutation in a large group of consecutive CVT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…It is noteworthy to mention that in adult patients not exhibiting hematologic criteria for MPN, venous thrombotic complications (especially splanchnic and cerebral thrombosis) may be the only symptom of the disease. In fact, the reported incidence of positivity to the JAK2 V617F mutation in those patients ranges from 12% to 74% in the presence of splanchnic vein thrombosis; it is estimated to be around 4% in presence of CSVT 5 . Most important, the finding of the JAK2 V617F mutation in patients with CSVT was associated with a recurrence risk of about 30%, supporting the need for a systematic screening 5 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is noteworthy to mention that in adult patients not exhibiting hematologic criteria for MPN, venous thrombotic complications (especially splanchnic and cerebral thrombosis) may be the only symptom of the disease. In fact, the reported incidence of positivity to the JAK2 V617F mutation in those patients ranges from 12% to 74% in the presence of splanchnic vein thrombosis; it is estimated to be around 4% in presence of CSVT 5 . Most important, the finding of the JAK2 V617F mutation in patients with CSVT was associated with a recurrence risk of about 30%, supporting the need for a systematic screening 5 …”
Section: Discussionmentioning
confidence: 97%
“…The JAK2 V617F mutation (c.1849G>T, p.Val617Phe) is a somatic gain‐of‐function mutation 7 . Its presence is a major diagnostic criterion for Philadelphia chromosome‐negative MPN 5 . This disorder is characterized by extensive proliferation of multipotent myeloid progenitor cells, including chronic myelomonocytic leukemia, polycythemia vera, essential thrombocythemia, and primary myelofibrosis 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High 2 Case Reports in Hematology clinical awareness is warranted to identify an underlying MPN in order that a prompt treatment is initiated (e.g., antiplatelet, cytoreductive, and phlebotomy) [24,25]. While some studies have suggested routine screening for JAK2 V617F in patients presenting with stroke and/or cerebral venous thrombosis (CVT) [26], given the lower risk of thrombosis in CALR-and MPL-mutated MPN patients and the near absence of these mutations in CVT cohorts [27,28], wider evaluation of mutation status might be reserved for those patients with sustained abnormal blood count findings. Detection of MPN-associated mutations is achieved by a number of technological approaches including Sanger sequencing, allele-specific PCR, melt curve analysis, capillary electrophoresis, pyrosequencing, digital PCR, and nextgeneration sequencing [29].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Testing for JAK2 mutation is also required in patients with recurrent thrombosis receiving anti-vitamin K. 13 A significant prevalence of the presence of this mutation in patients with deep vein thrombosis has not been established.…”
Section: Factorsmentioning
confidence: 99%